THE IMPACT OF INTEGRATIVE LEARNING: DEEP LEARNING WITH SPEDOMATIK MEDIA ON ENHANCING CRITICAL THINGKING SKILLS IN ELEMENTARY EDUCATION - Aprilia Nur Widyanti; Achmad Buchori; Ida Dwijayanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the impact of interactive learning using Deep Learning integrated with Spedomatik Media on enhancing critical thinking skills in elementary school students. The research was conducted with second-grade students at SDN 1 Sumberagung, utilizing a quasi-experimental design with a one-group pretest-posttest method. The findings revealed that the implementation of Deep Learning with Spedomatik Media significantly improved students' critical thinking skills. Pretest results showed that none of the students met the minimum competency criteria (KKTP), while posttest results indicated an 80% pass rate. Statistical analysis, including t-tests and regression analysis, demonstrated that the approach contributed 60.4% to the improvement of students' critical thinking abilities. Furthermore, the study found that the application of this approach fostered active participation, reflection, and collaborative learning, which are essential for critical thinking development. The results of this research suggest that interactive learning strategies, such as Deep Learning with Spedomatik Media, are effective tools in enhancing critical thinking skills and should be incorporated into elementary education to meet the demands of 21st-century learning.